A relação entre queixas de memória e fatores cognitivos e afetivos em idosos saudáveis - Andrade, Morgana do Nascimento (2015)
A number of studies have indicated that healthy elderly show subjective memory complaints, something whose meaning is not fully understood yet. The present research has aimed to analyze the neurocognitive profile of healthy elderly with or without memory complaints. The research was carried out with 69 healthy elderly aged around 66 years (DP = 5.86), divided into two groups: the ones who reported worsening of their memories over the last five years and the ones who did not. The results indicated higher impairment of prospective than retrospective memory. The study showed that the subjective memory complaints are strongly related to the symptoms of depression and anxiety. The elderly who reported worsening of memory have a higher degree of depression than the ones who did not report memory problems and do not have anxiety symptoms. It is concluded that the affective components may be better predictors of subjective memory complaints than the cognitive components.